KEPIMPINAN STRATEGIK RASULULLAH S.A.W.: KAJIAN PERLAKSANAANYA OLEH KAGAT: PROPHETIC STRATEGIC LEADERSHIP: A STUDY OF ITS IMPLEMENTATION BY KAGAT - Abdul Ghani Azmi, Ilhaamie; Ahmad Zaighu, Abdul Ghani (Online Journal of Islamic Management and Finance (OJIMF), 2021)
Muhammad s.a.w. is a man free of sin. As a leader, he should be made an example of and guidelines for Muslims, no matter where they are. This study is a historical research aims to study the strategic leadership of Prophet s.a.w in the battle of Badr. It is found out from the literature review that there are eleven strategic leadership of Prophet s.a.w. which are prayer and supplication, jihad motivation, calling for an urgent meeting, qiamullail, strengthening the bonds of brotherhood, appointing temporary leadership, sending some troops and intelligence unit, creating a peace agreement, understanding the geographical location of Badr battle, examining the power of the enemy and creative in planning the latest warfare techniques. A questionnaire was developed and distributed to KAGAT members to examine how far their strategic leaders have been implementing battle strategies that were practiced by Prophet s.a.w. This study found that majority of the respondents perceive that qiamullail is the most practiced by their strategic leaders and this is followed by pledge allegiance with the companions to equally fight and defend the truth and to appoint temporary leaders. This shows that these three practices are important in ensuring success will be obtained.